Number of People in the United States Experiencing Ambulatory and Independent Living Difficulties - Siordia, Carlos (2014)
Estimating the characteristics of the “disabled” population is necessary for some governments and of interest to health researchers concerned with producing disability prevalence rates. Because generating easy-to-understand estimates of disability in the population is important, this article provides US population estimates for two disability-related measures by using the 2009 to 2011 American Community Survey Public Use Microdata Sample file. The number of people who have “independent living” and “ambulatory” difficulties is calculated from a sample of 9,204,437 (representing > 309 million people). The percentage for “disabled” is found to vary by: racial-ethnic category, sex, age, citizenship status, educational attainment, and state-level regions divided by weather.